2022
DOI: 10.3389/fimmu.2021.761893
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ-Specific Recombinant Human Monoclonal Antibodies Allow for In-Depth Analysis of HLA-DQ Epitopes

Abstract: HLA-DQ donor-specific antibodies (DSA) are the most prevalent type of DSA after renal transplantation and have been associated with eplet mismatches between donor and recipient HLA. Eplets are theoretically defined configurations of surface exposed amino acids on HLA molecules that require verification to confirm that they can be recognized by alloantibodies and are therefore clinically relevant. In this study, we isolated HLA-DQ specific memory B cells from immunized individuals by using biotinylated HLA-DQ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…To confirm the impact of allele-specific solvent accessibility experimentally, binding analyses of HLA epitope-specific monoclonal antibodies to HLA as applied by Bezstarosti et al may be informative (36). Following the hypothesis, antibodies against antibody-verified Eplets with a wide distribution of surface accessibility (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the impact of allele-specific solvent accessibility experimentally, binding analyses of HLA epitope-specific monoclonal antibodies to HLA as applied by Bezstarosti et al may be informative (36). Following the hypothesis, antibodies against antibody-verified Eplets with a wide distribution of surface accessibility (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Critical residues defining serotypes or determining epitopes of HLA class II products were identified by similar approaches for HLA‐DR, 36–43 DQ 43–45 and DP 46–48 . Many of the epitopes defined in early studies were identified by non‐human mAbs; additional work confirmed that these same epitopes were also identified by both, allo‐antisera and mAbs of human origin 6,7,49,50 …”
Section: Introductionmentioning
confidence: 91%
“…[46][47][48] Many of the epitopes defined in early studies were identified by non-human mAbs; additional work confirmed that these same epitopes were also identified by both, allo-antisera and mAbs of human origin. 6,7,49,50 The simultaneous application of molecular typing methods and serologic testing in IHIW exercises allowed inference of which amino acids at polymorphic positions in the HLA class I and class II proteins, may determine epitopes recognized by sets of mAbs or by clusters of alloantibody reagents evaluated in the 12th 4,5 and 13th 6,7 IHIW. In the 13th IHIW the systematic computational analyses for examination of the mAbs and allo-antisera reactivity allowed mapping the putative epitopes recognized by serologic reagents.…”
Section: Introductionmentioning
confidence: 99%
“…For these eplets, previously published SAB data were re-analyzed to determine the uniquely shared residues and subsequently the possible eplets, which led to proposed new definitions of these reactivity patterns. The list of HLA class II antibody-verified eplets and antibody-verified reactivity patterns including literature references (43)(44)(45)(46)(47)(48)(49)(50) are depicted in Tables 6 and 7 respectively.…”
Section: Critical Review Of All Evidence For Antibody Verification Status Of Eplets In the Hla Epitope Registrymentioning
confidence: 99%